Pengembangan Game Edukatif Berbasis Pendekatan Etnomatematika Pada Kebudayaan Jawa Timur - Andini Safitri; Sumartono Sumartono; Windi Setiawan (LPPM Institut Pendidikan Nusantara Global, 2026)
Mathematics learning in Indonesia continues to face challenges, particularly in improving students' learning motivation. This study aimed to develop an educational game based on an ethnomathematics approach using East Javanese culture and to evaluate its feasibility and effectiveness in increasing elementary students' learning motivation. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analyze, Design, Development, Implementation, and Evaluation stages. The product was implemented with 26 fourth-grade students at UPT SD Negeri 327 Gresik. Data were collected through expert validation, learning motivation questionnaires, and pretest–posttest instruments, then analyzed using descriptive statistics, normality tests, and paired-sample t-tests. The developed game was categorized as highly feasible based on expert validation. The statistical analysis indicated a significant difference between pretest and posttest scores (p = 0.001 < 0.05), demonstrating that the educational game effectively improved students' learning motivation. Therefore, the ethnomathematics-based educational game can serve as an innovative and culturally relevant mathematics learning medium to support elementary school learning.